Estudio de los factores de riesgo psicosociales e implementación de planes de mejora para la Fundación General Ecuatoriana, en el período noviembre – julio del 2015 - Herrera Coronado, Gabriela Carolina (2016)
The project was carried out in the General Ecuadorian Foundation, during the period November 2014 to July 2015. The participants were 27 workers on the payroll consisting of the organization, being considered as the direct beneficiaries of the project. The main purpose was to identify psychosocial risk, in order to develop improvement plans, which allow to reduce the effects of these risks and foster a culture of prevention and control of them. The overall design was that the project is encompassed in a process that began with the diagnosis, in which the emerging problem was detected; after this psychosocial risk measurement was made through Psychosocial Factors Questionnaire of Navarra; then he proceeded to the analysis of results and the development of improvement plans; improvement plans were implemented; and it was completed with the process of monitoring and controlling the project. With the enforcement of the project, significant changes were obtained on how to prevent psychosocial risks in the organization, as the awareness of the importance and impact that these hazards cause both the mental, physical and social health of workers was achieved, and the level of organizational productivity. In addition, he managed to continue with the implementation of the workshops formulated in the improvement plans.